Provable security : 10th International Conference, ProvSec 2016, Nanjing, China, November 10-11, 2016, proceedings /: 10th International Conference, ProvSec 2016, Nanjing, China, November 10-11, 2016, proceedings. (2016) - Unknown
No abstract available